New hybrid procedures in treating occluded arteriovenous hemodialysis grafts - Bachleda, Petr; Janeckova, Jana; Xinopulos, Pavel; Smakal, Oldrich (Biomedical papers, 2016)
Backround. The use of arteriovenous graft is indicated in patients if the subcutaneous venous bed is exhausted or unsuitable for arteriovenous fistula creation. The leading cause of failure of a prosthetic arteriovenous hemodialysis-access graft is venous anastomotic stenosis causing thrombosis of the graft. A number of surgical techniques and endovascular tools have been used to treat this stenosis and thrombosis. None have yet proven to be ideal. This study was designed to evaluate the results of hybrid treatment of arteriovenous graft thrombosis associated with venous anastomotic stenosis.Methods: Over the period 2013-2014, we treated 16 AVG occlusions. Immediately after the diagnosis of occlusion was made, the patients underwent thrombectomy using a Fogarty catheter. After thrombectomy, a diagnostic fistulogram was performed and if VAG stenosis was confirmed, it was treated with balloon angioplasty and stent graft introduction. Lesions were dilated to reduce the stenosis in the treated area to less than 25%.Results: Primary patency after 12 months was 32.8%. Primary assisted patency was 44.7%, secondary patency was 47.6%. Restenosis of the stent graft was seen in two patients. Recurring AVG occlusion was observed in four patients. The average number of interventions to maintain AVG patency was 1.18 per patient/1 year of dialysis.Conclusion: Treatment of AVG thrombosis due to VAG stenosis by hybrid procedure proved to be effective and improved secondary patency.
Keywords: arteriovenous graft for hemodialysis (AVG); venous anastomotic stenosis (VAG); AVG thrombosis; surgical thrombectomy; stent graft